Influence of local lattice distortions on electrical transport of refractory high entropy alloys. (September 2019) - Mu, Sai; Wimmer, S.; Mankovsky, S.; Ebert, H.; Stocks, G.M.
Abstract: We employ first-principles alloy theories to assess the influence of local lattice distortions on the electronic transport of six body-centered cubic high-entropy alloys. We find weak disorder smearing of bands in the ideal lattice due to the similar number of valence electrons among alloying elements. Allowing relaxation, we demonstrate that local distortions in NbMoTaW and VNbMoTaW are small while they are anomalously large in HfNbTiZr, HfNbTaTiZr, VCrZrNb and CrNbTiVZr. The Fermi surfaces of the latter are strongly smeared by local distortions, leading to nearly-saturated resistivities. These findings address the important local relaxation effect on the electronic structure of high-entropy alloys. Graphical Abstract: Unlabelled Image